2017
DOI: 10.1002/asi.23872
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence query reformulations and search performance in health information retrieval: A multilevel modeling approach

Abstract: which provides a more extended understanding of the relationships among factors that influence query reformulation behavior and search performance. The multilevel modeling used in this study has practical implications for future query reformulation studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Session-aware query reformulation is involved in retrieval-based interactive systems, including dynamic IR systems , multi-turn Question Answering (QA) (Mensio et al, 2018), and dialogue systems (Cui et al, 2019). Several works studied the connections between search sessions, intentions in query reformulation, and search behavior (Lu et al, 2017;Liu et al, 2019b;Tamine et al, 2020). Among the major findings, we particularly mention the following: (1) query reformulation patterns can be observed in search sessions providing insights on the search process characteristics such as underlying search task stage (Tamine et al, 2020;Eickhoff et al, 2014) and success (Odijk et al, 2015); (2) during the session search, system's results often lead to a change in both user's knowledge and the complexity of subsequent queries (Eickhoff et al, 2014;Liu et al, 2019a); (3) user search process runs into sequential phases, specialization, and intent shift.…”
Section: Session-aware Query Reformulationmentioning
confidence: 99%
“…Session-aware query reformulation is involved in retrieval-based interactive systems, including dynamic IR systems , multi-turn Question Answering (QA) (Mensio et al, 2018), and dialogue systems (Cui et al, 2019). Several works studied the connections between search sessions, intentions in query reformulation, and search behavior (Lu et al, 2017;Liu et al, 2019b;Tamine et al, 2020). Among the major findings, we particularly mention the following: (1) query reformulation patterns can be observed in search sessions providing insights on the search process characteristics such as underlying search task stage (Tamine et al, 2020;Eickhoff et al, 2014) and success (Odijk et al, 2015); (2) during the session search, system's results often lead to a change in both user's knowledge and the complexity of subsequent queries (Eickhoff et al, 2014;Liu et al, 2019a); (3) user search process runs into sequential phases, specialization, and intent shift.…”
Section: Session-aware Query Reformulationmentioning
confidence: 99%
“…A 47-year-old man presented to the emergency room with left hypochondrium pain that had been evolving for 24 The task data and humanassessed sub-tasks Task, Task description, expert expected sub-tasks a set of candidate ones. Second, we also evaluate search strategy identification which consists in indicating if an issued query in context (based on previous queries in the session) mainly indicates either an exploration or an exploitation strategy.…”
Section: Problem-solving (Trpmed)mentioning
confidence: 99%
“…A number of previous user studies highlighted the impact of different task characteristics on users' query reformulations [24,34,38,43]. The results mainly revealed that: 1) the domain knowledge of the task doer significantly impacts query term changes; 2) the cognitive complexity of the task (e.g., simple, hierarchical, parallel) has a significant effect on users' query reformulation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Another category of work rather employed lab user studies to understand how different task characteristics impact users' query reformulations [15,17,18,28,31,32]. The results mainly revealed that: (1) the domain knowledge of the task doer significantly impacts query term changes.…”
Section: Query Reformulation Understandingmentioning
confidence: 99%